2014
DOI: 10.1002/ejp.593
|View full text |Cite
|
Sign up to set email alerts
|

Hypervigilance for innocuous tactile stimuli in patients with fibromyalgia: An experimental approach

Abstract: Background: Hypervigilance, i.e., excessive attention, is often invoked as a potential explanation for the observation that many individuals with fibromyalgia show a heightened sensitivity to stimulation in various sensory modalities, such as touch and hearing. Compelling evidence for this assumption is, however, lacking. The aim of the present study was to investigate the presence of somatosensory hypervigilance in patients with fibromyalgia. Methods: Fibromyalgia patients (n = 41) and a matched control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Although the small CI indicates robustness of the finding that the accuracy of detecting heart beats does not differ between FM patients and healthy controls, it is opposed to previous results showing increased pain sensitivity and amplified perception of painful and non-painful stimuli in FM patients (2,3,(7)(8)(9). The present finding, however, is in line with a number of studies, which failed to demonstrate prioritization of external innocuous stimuli in FM patients (4,41). In the study by Van Damme and colleagues (41), participants performed a tactile change detection task in which they had to detect whether there was a change between two consecutively presented patterns of tactile stimuli presented to various body locations.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Although the small CI indicates robustness of the finding that the accuracy of detecting heart beats does not differ between FM patients and healthy controls, it is opposed to previous results showing increased pain sensitivity and amplified perception of painful and non-painful stimuli in FM patients (2,3,(7)(8)(9). The present finding, however, is in line with a number of studies, which failed to demonstrate prioritization of external innocuous stimuli in FM patients (4,41). In the study by Van Damme and colleagues (41), participants performed a tactile change detection task in which they had to detect whether there was a change between two consecutively presented patterns of tactile stimuli presented to various body locations.…”
Section: Discussionsupporting
confidence: 55%
“…In line with this assumption, subsequent studies aimed to investigate the GHH with innocuous stimuli (e.g. 4,41). Other studies, however, interpreted the GHH as referring to aversive stimuli only (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It also has a large evidence-base that spans the emotion and pain literature (see e.g. Reduced pain threshold has been reported in individuals with persistent pain (Herren-Gerber et al, 2004) and is indicative of somatosensory hypervigilance (Van Damme et al, 2015). Second, each attentional bias test comprised 96 trials, which is arguably low and may have compromised the sensitivity of the test to detect bias change, but we think this is unlikely as other studies have successfully used similar trials per condition (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of clinical implications, the findings concerning threshold and tolerance are noteworthy. Reduced pain threshold has been reported in individuals with persistent pain (Herren-Gerber et al, 2004) and is indicative of somatosensory hypervigilance (Van Damme et al, 2015). This hypervigilance may lead to increased avoidance of pain-causing activities, deconditioning and depression, and increased likelihood of pain, creating a vicious circle Linton, 2000, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing fibromyalgia patients and healthy controls found no difference in their ability to detect innocuous tactile stimuli (Vandenbroucke et al, 2014;Van Damme et al, 2014), and/or observed that only NA predicted daily symptom reports (Mussgay et al, 1999;Schaefer et al, 2012). Other studies investigating attentional processing of bodily sensations themselves provide some evidence for a relationship between attention to the body and symptom reporting, although also implicate avoidance of bodily sensations Brown et al, 2010).…”
Section: Interoceptive Hypervigilance Thresholds and Awarenessmentioning
confidence: 99%